2011
DOI: 10.1111/j.1461-0248.2011.01598.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in forest productivity across Alaska consistent with biome shift

Abstract: Global vegetation models predict that boreal forests are particularly sensitive to a biome shift during the 21st century. This shift would manifest itself first at the biome's margins, with evergreen forest expanding into current tundra while being replaced by grasslands or temperate forest at the biome's southern edge. We evaluated changes in forest productivity since 1982 across boreal Alaska by linking satellite estimates of primary productivity and a large tree-ring data set. Trends in both records show co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
274
4
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 310 publications
(313 citation statements)
references
References 49 publications
29
274
4
1
Order By: Relevance
“…A consistent long-term control of boreal forest growth by summer moisture availability has been observed in the drier continental interiors of Alaska and North-Western Canada where increased tree growth is stimulated by cooler and wetter growing seasons [23,27,28]. Hence, warming in these boreal regions has often been associated with tree growth declines rather than with increases [23], consistent in cases with co-located NDVI browning trends [18].…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…A consistent long-term control of boreal forest growth by summer moisture availability has been observed in the drier continental interiors of Alaska and North-Western Canada where increased tree growth is stimulated by cooler and wetter growing seasons [23,27,28]. Hence, warming in these boreal regions has often been associated with tree growth declines rather than with increases [23], consistent in cases with co-located NDVI browning trends [18].…”
Section: Introductionmentioning
confidence: 58%
“…Using Maximum Covariance Analysis to isolate the coupled trends in winter snowpack (maximum SWE), soil moisture availability (scPDSI) and summer NDVI in North America has shown that the temporal pattern of shared trends is strongly consistent with the temporal trajectory of regional-scale declines in NDVI, tree-ring growth, forest biomass and modeled productivity previously documented in the boreal region (e.g., [15,18,35,70,91]). Furthermore, the spatial patterns of the coupled trends suggest contrasting vegetation responses to declining snowpack accumulation in the Arctic shrublands and boreal forests since the early 1990s.…”
Section: Drivers Of Vegetation Greening and Browning Trendsmentioning
confidence: 91%
See 3 more Smart Citations